Lung cancer awareness and palliative care interventions implemented in low-and middle-income countries: a scoping review - Ugochinyere I. Nwagbara; Themba G. Ginindza; Khumbulani W. Hlongwana (BMC, 2020)
Abstract Background Lung cancer is the most diagnosed cancer worldwide. In low- and middle-income countries (LMICs), lung cancer is often diagnosed at a late stage due to poor knowledge and awareness of its signs and symptoms. Increasing lung cancer awareness is likely to reduce the diagnosis and treatment delays. The implementation of early palliative care has also been reported to improve a patient's quality of life, and even survival. The aim of this scoping review was to map evidence on lung cancer awareness and palliative care interventions implemented in sub-Saharan Africa (SSA) and other LMICs. Methods This scoping review was guided by Arksey and O'Malley's framework. Databases such as the EBSCOhost, PubMed, Science Direct, Google Scholar, World Health Organization (WHO) library and grey literature were used to perform systematic searches of relevant articles. The methodological quality assessment of included primary studies was assessed using the Mixed Method Appraisal Tool (MMAT). NVivo version 10 software was used to perform the thematic content analysis of the included studies. Results A total number of screened articles was 2886, with 236 meeting the eligibility criteria and 167 further excluded following abstract screening. Sixty-nine (69) articles qualified for full-article screening and 9 were selected for detailed data extraction and methodological quality assessment. Of the included nine studies, eight described at least one lung cancer warning signs and symptoms, while one described the effectiveness of palliative care for lung cancer. Eight articles recognized the level of lung cancer knowledge, risk factors awareness of warning signs and symptoms in LMICs, mostly Africa and Asia. Conclusions Most of the participants were aware of tobacco use as the major risk factor for lung cancer but lacked knowledge on the other pre-disposing risk factors. Evidence on palliative care is scarce, therefore, awareness interventions packaged with evidence on the value of timely access to palliative care services in improving the quality of life of the lung cancer patients and their families, are required.